Performance Analysis of Routing Protocols for Urban VANET Based on SUMO and NS2.35: https://doi.org/10.69692/SUJMRD0802303 - Phonekhamma, Chitnavanh; Chanthavong, Nino; Sengaphai, Khamkone; Thipphavong, Suphaivy; Dong, Wang (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
To make the dream of intelligent transportation systems come true, the development of the autonomous cars is considered as a tremendous disruptive innovation in the coming years. Vehicular ad hoc networks (VANETs) are being used as a tool for improving road safety by alarming the drivers about accidents occurred ahead of them or for providing internet access via gateways along the road. Due to highly dynamic nature of nodes in VANETs, designing a routing protocol for VANET is quite challenging compared to other networks environment. Researchers have suggested several routing algorithms for VANETs. Few routing algorithms are based on topology based whereas others have considered position based etc. As no standard scheme is available for choosing a routing protocol in VANETs, this paper gives an insight on how to choose a routing protocol depends on varying condition of traffic such as number of nodes on the roads and maximum speed of nodes. The popular protocols of Topology Based Routings and Position Based Routing have been chosen for analysis on varying traffic environment. All the protocols have been critically tested for different metrics such as packet delivery ratio and average end-to-end delay during the simulation. Simulation is carried out with the help of SUMO traffic simulator and open-source simulation tools NS2.35 network simulator. Simulation result show that Position Based Routing is performing better at low average end-to-end delay than Topology Based Routings, but Position Based Routing has the lowest possible performance in packet delivery ratio than Topology Based Routings.